Quality Control And More - Agnihotri, Jaya (International Journal of Pharmaceutical & Biological Archive, 2011)
In today?óÔé¼Ôäós scenario as new and better medicinal agents are being produced at an accelerated rate,the role of quality control chemist becomes challenging one. The quality control department becomes an important link in data analysis for newly launched products by a manufacturing company. To be effective, it must be supported by a team effort. Production failure causing rejection or recalls after market introduction are serious and can be easily detected and minimized by an effectively administered quality control system. Quality control system must be comprehensively designed, correctly implemented, fully documented and effectively monitored. Though the product is successful at research level, there are many constraints in scale up. At the same time more exacting and sophisticated analytical methods are being developed for evaluation. As a handful of data is available with quality control department, consistent and predictable performance of the product is expected.The current article reveals duties and responsibilities of quality control department.